2010
DOI: 10.1158/1078-0432.ccr-09-0694
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Angiogenesis Inhibitor BIBF 1120 in Patients with Advanced Solid Tumors

Abstract: Purpose: BIBF 1120 is an oral, potent angiokinase inhibitor targeting receptors of the vascular endothelial growth factors, platelet-derived growth factors, and fibroblast growth factors. This phase I, accelerated titration study assessed the maximum tolerated dose, safety, pharmacokinetics, and pharmacodynamic effects of BIBF 1120.Patients and Methods: Sixty-one patients with advanced cancers received BIBF 1120 in successive cohorts. Twenty-five received 50 to 450 mg once daily and 36 received 150 to 300 mg t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
169
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(206 citation statements)
references
References 23 publications
(24 reference statements)
25
169
0
3
Order By: Relevance
“…This approval was based on the LUME-Lung 1 trial, which demonstrated a significant improvement in OS to more than 1 year in patients with lung adenocarcinoma treated with nintedanib plus docetaxel versus docetaxel alone [90]. Phase I and II clinical studies initially demonstrated beneficial clinical effects with nintedanib monotherapy in advanced HCC, RCC, and CRC, and in addition to standard chemotherapy combination regimens in various tumor types, including prostate cancer and gynecologic malignancies [114][115][116][117][118][119][120][121][122]. Encouraging PFS data in OC have been reported (Table 2), and OS data for this indication are awaited [92].…”
Section: Current and Emerging Multitargeting Antiangiogenic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approval was based on the LUME-Lung 1 trial, which demonstrated a significant improvement in OS to more than 1 year in patients with lung adenocarcinoma treated with nintedanib plus docetaxel versus docetaxel alone [90]. Phase I and II clinical studies initially demonstrated beneficial clinical effects with nintedanib monotherapy in advanced HCC, RCC, and CRC, and in addition to standard chemotherapy combination regimens in various tumor types, including prostate cancer and gynecologic malignancies [114][115][116][117][118][119][120][121][122]. Encouraging PFS data in OC have been reported (Table 2), and OS data for this indication are awaited [92].…”
Section: Current and Emerging Multitargeting Antiangiogenic Agentsmentioning
confidence: 99%
“…Encouraging PFS data in OC have been reported (Table 2), and OS data for this indication are awaited [92]. Nintedanib is an orally available angiokinase inhibitor of VEGFR-1 to -3, PDGFR-a and -b, and FGFR-1 to -3, in addition to FLT-3 and Src [82,114,138]. Human tumor model studies show that nintedanib can reduce vessel density, vessel integrity, and tumor growth via effects on endothelial and smooth muscle cells, pericytes, and tumor cells [82].…”
Section: Current and Emerging Multitargeting Antiangiogenic Agentsmentioning
confidence: 99%
“…The most frequently reported drug-related adverse events were gastrointestinal events (i.e., nausea, vomiting, and diarrhea). Early signs of effi cacy were observed, including one complete response in a patient with renal cell cancer and 2 PRs in a patient with renal cell cancer and a patient with colorectal cancer ( 79 ). In another open-label, phase I dose-escalation trial of BIBF1120 in Japanese patients with advanced NSCLC, SD for 2 or more treatment courses was reported in 76% of patients ( n = 16; ref.…”
Section: Drugs and Phase I Datamentioning
confidence: 99%
“…Inhibition of tumor growth was demonstrated in vivo in several xenograft models [113] and clinically in refractory tumors, demonstrating to be active in colorectal cancer, renal cancer and hepatocarcinoma [114]. Nintedanib in combination with docetaxel is indicated in locally advanced or metastatic lung adenocarcinoma patients who failed a first-line treatment.…”
Section: Nintedanibmentioning
confidence: 99%